Evaluation of complications and sequelae after surgical treatment of female pelvic organ prolapse with synthetic graft placement - Tran, Quang Hien (Tạp chí Y học lâm sàng Bệnh viện Trung Ương Huế, 2024)
Introduction: Pelvic organ prolapse is a common condition in Vietnam. At An Giang obstetrics and pediatrics hospital, vaginal mesh surgery for the treatment of female pelvic organ prolapse has recently been introduced, which is a new technique for the hospital and requires evaluation and research. This study evaluates the treatment results of female pelvic organ prolapse by surgical placement of a synthetic vaginal mesh at An Giang obstetrics and pediatrics hospital in 2020-2021. Methods: Cross-sectional descriptive and prospective study. All women diagnosed with pelvic organ prolapse stage II or higher according to POP-Q criteria underwent vaginal mesh placement surgery. Results: The study results of 47 cases of pelvic fractures. There was 1 case of bladder perforation, accounting for 2%, and 2 cases of intraoperative bleeding, accounting for 4.3%. After surgery, no complications were detected for 1 month. After 3 months, there were 2 cases of graft exposure during re-examination due to painful intercourse, accounting for a rate of 4.3%. No complications were recorded after 6 months, and 2 cases of graft exposure during re-examination after surgery 3 months ago have been successfully treated. 87.2% of patients resumed sexual activity at this stage and no complications were reported. 98% of patients expressed satisfaction with this surgical method and are excited to confidently recommend this surgical method to other women. 2% are concerned about the cost of the mesh. Conclusion: The effectiveness of the surgical method of placing a synthetic vaginal graft for the treatment of female pelvic organ prolapse achieves a success rate of 95.7%. 98% of patients express satisfaction with this surgical method and are enthusiastic about recommending this surgical method to other women.